Editorial: English - Santos, Gildenir Carolino; Passos, Rosemary (Universidade Estadual de Campinas, 2008)
Starting our 2006 activities, once more we would like to express our satisfaction to have you with us participating in this journal through your reading and collaborating with articles that contribute for the enrichment of this publication day by day. This year, several subjects that started to be investigated on previous years, got relevance since the development of more specific researches provide continuity to theoretical and methodological studies. We begin with three articles and one report of experience in the Thematic Area Librarianship & Information Science, when the evolution of the use of libraries in several knowledge areas is dicussed, as well as its influence in the information and knowledge transfer, that demand acquisition of informational competences by users in order to use the resources available in libraries. This makes possible to individuals to proceed with the descriptive representation and organization of knwoledge acquired in their search of information in the knowledge society. This section also brings some bibliotherapeutic studies made to verify the level of acceptance of reading as leisure activity from the part of inpatients in a medical clinic...